Mullah omar and robespierre: essays in the politics of ideas - "Rao, Parsa Venkateshwar" (New Delhi, 2005)
Essays on politics, history, philosophy, India and cultural interaction India and West. by a leading journalist, written in Chennai.
Keywords: Afganistan-Politics and government